Vestibular evoked myogenic potentials evoked by multichannel cochlear implant - influence of C levels. - Jin Y; Shinjo Y; Akamatsu Y; Ogata E; Nakamura M; Kianoush S; Yamasoba T; Kaga K (Acta Oto-Laryngologica, 2008)
CONCLUSIONS: This study showed that vestibular evoked myogenic potentials (VEMPs) evoked by cochlear implant (CI), could be related to the comfortable level (C level), particularly in the channels that are closer to the apical turn of the cochlea. OBJECTIVE: The purpose of this study was to investigate the correlation between VEMPs and C level of each channel. SUBJECTS AND METHODS: We investigated 24 children who underwent cochlear implantation. VEMPs were recorded from the operated ears with the CI switched 'off' or 'on'. To investigate the correlation between VEMPs and C level, we selected 13 patients with Nucleus 24 (SPrint), and divided them into group A (normal VEMPs) and B (absence of VEMPs). In these children, all the 22 electrodes were active, and were mapped in the same frequency range for each channel. RESULTS: Twenty children (83%) showed no VEMPs with the CI 'off'. Among them, 10 elicited VEMPs with the CI 'on', but the other 10 did not. In all channels, the mean C levels of CI were higher in group A than in group B. The p values in channels 1-12 were >0.10, in channels 13-16 were 0.06-0.09, and in channels 17-22 were 0.05-0.06, which were lower but not statistically significant.